Preference Communication and Leadership in Group Decision-Making - Seda Ertac; Mehmet Y. Gurdal (Koç University-TÜSİAD Economic Research Forum (ERF), 2013)
We report results from a laboratory experiment that explores the effects of preference communication and leader selection mechanisms in group decision-making. In a setting where all members of a group get the same payoff based on the group leader's decision of how much risk to take, we study the effects of two treatment variables: (1) whether group members can communicate their preferences to the leader, (2) whether the leader is exogenously appointed or voluntarily self-selects into the position. We find that the leader selection mechanism crucially affects the integration of group preferences into the leader's decision: the communicated preferences have a significant effect on the actual group decision only when the leader is appointed. We also find that preference communication by non-leaders is frequently strategic.
Keywords: C91; C92; D81; J16; 330; group decision-making; risk; leadership; delegation; advice; information; experiments